A distributed event-triggered algorithm for constrained economic dispatch problem via virtual communication - Wu, Yuyang; Wang, Xiyuan; Yan, Li; He, Xiaochuan; Dai, Hao (International journal of electrical power & energy systems, 2024)
A new distributed discrete-time event-triggered optimization algorithm is proposed based on the Newton–Raphson iterative method and the consensus algorithm in this paper. With the aid of virtual communication strategy, the proposed algorithm can solve economic dispatch problem with power output constraints under undirected and connected network. Moreover, the waste of network resources can be reduced by adopting event-triggered communication strategy. In addition, the linear convergence of the algorithm is strictly proved by the discrete Lyapunov stability theory. Finally, three numerical simulation examples are given to show the effectiveness and advantages of the proposed algorithm. •A consensus-based discrete-time event-triggered optimization algorithm is proposed.•A virtual communication strategy is proposed that can ensure the capacity constraint is satisfied.•Communication resources are saved by introducing event-triggered communication strategy.•The Zeno behavior can be naturally excluded by adopting discrete iterative scheme.